Determination of mass stopping power, stopping cross section and effective atomic number of standard amino acids for relativistic electron interactions. (March 2019) - Babu, S. Ramesh; Badiger, N.M.
Abstract: The electron interaction parameters like mass stopping power and hence the stopping cross section of 17 standard amino acids are measured by performing transmission experiments in a narrow beam geometry set-up with Si (Li) detector coupled to an 8K Channel Multichannel Analyzer. Substituting these experimentally measured mass stopping power in the empirical relation between mass stopping power and atomic number of organic elements, we determined the remaining electron interaction parameters namely effective atomic number of the standard amino acids for relativistic electron interaction. Our results are compared with the theoretical values and with the values available in literature and are found to agree within the experimental uncertainties. Experimentally determined effective atomic numbers of amino acids for electron interactions are also compared with those for photon interaction at the given energies. Highlights: Experimental determination of Zeff of amino acids for electron interactions of energies till 10 MeV. Experimental data of all 17 standard amino acids using simple spectroscopic method. Energy range of measurement around the highly representative mip region wherein no experimental data are available. Comparison of experimental results with the theoretical one to check their validity.